Ranking of romantic acts among Cape Verdean and Portuguese students
College students, 119 men and 116 women, from Cape Verde and Portugal ranked the importance of romantic acts. Comparisons between men and women and between Cape Verdean and Portuguese students showed no significant differences. An interesting finding was that "making love" was ranked the most important romantic act by men but only fifth by women in Portugal (behind cuddling, gazing, love letters, and kissing), whereas it was ranked third for both sexes in Cape Verde.